On-sun testing of a 1 MWth quartz tube bundle solid particle solar receiver. (June 2022) - Yu, Yupu; Hu, Feng; Bai, Fengwu; Wang, Zhifeng
Abstract: Solid particle solar receivers (SPSRs) are receiving increasing attention for the high operation temperature, which offers the potential for reducing the cost of solar thermal power plants. The configurations of previous SPSRs suffer from the barriers of complicated structures and inferior thermal performances. There is an urgent demand to develop a SPSR lumped of a simple configuration, a lower cost and superior thermal performances. In this paper, a quartz tube bundle SPSR with a thermal power capacity of 1 MW was designed and developed. On-sun tests were conducted based on a solar power tower plant and the total on-sun operation time has exceeded 100 h until the writing of the paper. The experimental results show that the receiver configuration has strong resistance to the non-uniform incident irradiances, even to the transient overcast sky condition. The maximum outlet temperature of 872 °C was obtained with 59 heliostats in operation, direct normal irradiance of 865 W / m 2 and residual time of 351 s. The maximum temperature increase per length reached 324 °C / m .